Class and Other Identities: Gender, Religion and Ethnicity in the Writing of European Labour History - Haiven, Judy (Relations industrielles / Industrial Relations, 2004)
The book, "Class and Other Identities: Gender, Religion and Ethnicity in the Writing of European Labour History," edited by Lex Heerma van Voss and Marcel van der Linden, is reviewed.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Economic theory; Essays; Ethnicity; Gender; History; Labor Unions; Labor relations; Religion; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social classes